EFFECT OF SUPERVISION ON EMPLOYEE PERFORMANCE AT PT. INDO SUHARJAYA/ NARMA TOSERBA - Anita Novia Lumi; Maria Yosef (ABNUS Publisher, 2022)
This study aims to determine the effect of supervision variable (X) on employee performance variable (Y) PT. Indo Suharjaya/Narma Toserba, and this study uses a quantitative method with an associative approach. The data sources used consisted of primary data, namely data obtained directly from research respondents through questionnaires, interviews, observations. The population and sample in this study were employees of PT. Indo Suharjaya/Narma Toserba Padurenan has as many as 70 employees, the research method used is descriptive statistical analysis method with Likert scale method. The test was carried out using the help of SPSS version 21. The results of this study 1) this correlation coefficient indicates that there is a relationship between supervision and employee performance of 0.716 with a significant level of 0.000. This means that supervision has a positive relationship with employee performance with a strong correlation degree at PT. Indo Suharjaya/Narma Padurenan Department Store. Based on the results of the t-test, it is known that the supervisory variable has a significant effect on employee performance because the tcount (8.462) > t table (1.666) then the supervision variable has an effect on employee performance. Analysis of the coefficient of determination. The adjusted R-Square value obtained is 0.513, indicating about 51.3% of the influence of supervision on employee performance while the remaining 0.48.7 indicates that around 48.7% is influenced by other variables not included in this research model.